Combating multidrug-resistant Plasmodium falciparum malaria. - Thu, A; Phyo, A; Landier, J; Parker, D; Nosten, F (Wiley, 2017)
Over the past 50 years, Plasmodium falciparum has developed resistance against all antimalarial drugs used against it: chloroquine, sulphadoxine-pyrimethamine, quinine, piperaquine and mefloquine. More recently, resistance to the artemisinin derivatives and the resulting failure of artemisinin-based combination therapy (ACT) are threatening all major gains made in malaria control. Each time resistance has developed progressively, with delayed clearance of parasites first emerging only in a few regions, increasing in prevalence and geographic range, and then ultimately resulting in the complete failure of that antimalarial. Drawing from this repeated historical chain of events, this article presents context-specific approaches for combating drug-resistant P. falciparum malaria. The approaches begin with a context of drug-sensitive parasites and focus on the prevention of the emergence of drug resistance. Next, the approaches address a scenario in which resistance has emerged and is increasing in prevalence and geographic extent, with interventions focused on disrupting transmission through vector control, early diagnosis and treatment, and the use of new combination therapies. Elimination is also presented as an approach for addressing the imminent failure of all available antimalarials. The final drug resistance context presented is one in which all available antimalarials have failed; leaving only personal protection and the use of new antimalarials (or new combinations of antimalarials) as a viable strategy for dealing with complete resistance. All effective strategies and contexts require a multipronged, holistic approach.